Synthesis, Characterization and Antimicrobial Activity of Some Novel 1,4-dihydropyrano[2,3-c]pyrazole-5-carbonitrile Derivatives (JOURNAL OF ADVANCES IN CHEMISTRY, 2015)
The present research work deals with synthesize a series of various substituted benzothiazole containing 6-amino- 4-(substituted aryl)- tetrahydropyrano[2,3-c]pyrazole-5-carbonitrilic by reacting 2-mercaptobenzothiazole with hydrazine hydrate to synthesize hydrazine derivatives of benzothiazole (1), which then reacted with Î²- keto ester to develop pyrazole derivative (2), and then finally reacted with malononitrile and different aromatic aldehydes to obtain the final compounds (3a-3f). The structures of the intermediates and final compounds are assigned by using FTIR and 1H-NMR. The final compounds were screened for their antibacterial activity against four tested bacteria as G+ and G- using a well diffusion method. The results of antibacterial activity exhibited that the species Klebsiella pneumonia was the most effected types, while Pseudomonas aeruginosa was least the effected in general.Â